Disembedding performance and eye gaze behavior of adolescents with Autism Spectrum Disorder. (October 2019) - Black, Melissa H.; Vaz, Sharmila; Parsons, Richard; Falkmer, Torbjorn; Tang, Julia S.Y; Morris, Susan; Lee, Hoe; Falkmer, Marita
Highlights: Superiority in particular visuo-spatial tasks, such as disembedding is commonly observed in Autism Spectrum Disorders (ASD). Gaze patterns of adolescents with and without ASD were compared during a disembedding task. Adolescents with ASD showed atypical gaze patterns compared to their typically developing peers. Adolescents did not show superiority in the disembedding task compared to typically developing adolescents. Abstract: Background: Atypical visual perception in individuals with Autism Spectrum Disorders (ASD) may contribute to superiority in disembedding tasks. Gaze behavior has provided some insights in to mechanisms underlying this purported superiority in children, however evidence is limited and requires additional investigation. Method: The performance and gaze behavior of 27 adolescents with ASD and 27 matched typically developing (TD) peers were examined during the Figure Ground Subtest of the Test of Visual Perception Skills-third edition (TVPS-3). Results: Compared to their TD counterparts, adolescents with ASD were no different in accuracy, however, had a longer response time. Differences in gaze behavior were also observed, characterized by adolescents with ASD spending less time viewing the incorrect and target figures, and spending a greater proportion of time viewing irrelevant areas of the stimuli compared to TD adolescents. Conclusions: Results suggest that while altered visual perception was observed, this did not contribute to superiority in disembedding tasks in adolescents with ASD. Future research is required to elucidate conditions under which altered visual perception may contribute to behavioral superiority.